Multi-parameter optimization of aza-follow-ups to BI 207524, a thumb pocket 1 HCV NS5B polymerase inhibitor. Part 2: Impact of lipophilicity on promiscuity and in vivo toxicity. Issue 5 (1st March 2015) - Beaulieu, Pierre L.; Bolger, Gordon; Deon, Dan; Duplessis, Martin; Fazal, Gulrez; Gagnon, Alexandre; Garneau, Michel; LaPlante, Steven; Stammers, Timothy; Kukolj, George; Duan, Jianmin
Graphical abstract